Paediatric empyema: worsening disease severity and challenges identifying patients at increased risk of repeat intervention. Issue 9 (24th March 2020) - Haggie, Stuart; Gunasekera, Hasantha; Pandit, Chetan; Selvadurai, Hiran; Robinson, Paul; Fitzgerald, Dominic A
Abstract : Objective: Empyema is the most common complication of pneumonia. Primary interventions include chest drainage and fibrinolytic therapy (CDF) or video-assisted thoracoscopic surgery (VATS). We describe disease trends, clinical outcomes and factors associated with reintervention. Design/setting/patients: Retrospective cohort of paediatric empyema cases requiring drainage or surgical intervention, 2011–2018, admitted to a large Australian tertiary children's hospital. Results: During the study, the incidence of empyema increased from 1.7/1000 to 7.1/1000 admissions (p<0.001). We describe 192 cases (174 CDF and 18 VATS), median age 3.0 years (IQR 1–5), mean fever duration prior to intervention 6.2 days (SD ±3.3 days) and 50 (26%) cases admitted to PICU. PICU admission increased during the study from 18% to 34% (p<0.001). Bacteraemia occurred in 23/192 (12%) cases. A pathogen was detected in 131/192 (68%); Streptococcus pneumoniae 75/192 (39%), S. aureus 25/192 (13%) and group A streptococcus 13/192 (7%). Reintervention occurred in 49/174 (28%) and 1/18 (6%) following primary CDF and VATS. Comparing repeat intervention with single intervention cases, a continued fever postintervention increased the likelihood for a repeat intervention (OR 1.3 per day febrile; 95% CI 1.2 to 1.4, p<0.0001). Younger age, prolonged fever preintervention and previous antibiotic treatment were not associated with initial treatment failure (all p>0.05). Conclusion: We report increasing incidence and severity of empyema in a large tertiary hospital. One in four patients required a repeat intervention after CDF. Neither clinical variables at presentation nor early investigations were able to predict initial treatment failure.